The Determinants of Australian Exchange Rate: A Time Series Analysis - Syed Muhammad Atif; Moldir Sauytbekova; James Macdonald (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The paper analyzes Australian exchange rate and its determinants by providing an insight into the economic and non-economic factors. By drawing a comparison between quarterly and annual data over the period of 1975 to 2012, it is suggested that Australia's trade components and macroeconomic indicators such as output and liquidity relative to the US, play a significant role in determination of its exchange rates. However, interest rate and inflation appear insignificant in this relationship. The study also emphasizes on the pertinence of unobservable effects such as political events and external shocks in influencing the exchange rate. Engle-Granger Cointegration test exhibits a long run relationship between exchange rate and its determinants, and corroborates the substantial role of macroeconomic indicators in diminishing the uncertainty in foreign exchange market.
Keywords: C22; F31; 330; Exchange Rate; Backward Elimination; Exchange rate